The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.3354/dao002039
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in hepatopancreatic cells of the prawn Palaemon serratus induced by exposure to acutely toxic cadmium concentrations

Abstract: Accumulation of cadmium in the hepatopancreas of the common prawn Palaemon serratus (Pennant) and ultrastructural changes m hepatopancreatic cells were examined after exposure to 3 cadmium concentrations (5, 25.50 ppm) for 44 h. Accumulation of cadmium Ions in 50 ppm solution was 800 % higher compared with control specimens. Absorptive and fibrillar cells (R-and F-cells) in the hepatopancreas were affected by cadmium ions at the ultrastructural 1evel.The ultrastructural changes observed suggest impairment of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Several effects of cadmium and zinc on the energy expenditure in terrestrial, freshwater and marine invertebrates have been reported. Cadmium reduces the growth efficiency in P. scaber (van Capelleveen, 1987) and impairs ion transport, absorption and protein synthesis in the hepatopancreas of the prawn Palaemon serratus (Papathanassiou and King, 1986). Furthermore, cadmium affects the oxidative carbohydrate metabolism in the freshwater crab Barytelphusa guerini and in the freshwater clam Anodonta cygnea (Reddy et al, 1989;Hemelraad et al, 1990).…”
Section: Energy Reservesmentioning
confidence: 97%
See 1 more Smart Citation
“…Several effects of cadmium and zinc on the energy expenditure in terrestrial, freshwater and marine invertebrates have been reported. Cadmium reduces the growth efficiency in P. scaber (van Capelleveen, 1987) and impairs ion transport, absorption and protein synthesis in the hepatopancreas of the prawn Palaemon serratus (Papathanassiou and King, 1986). Furthermore, cadmium affects the oxidative carbohydrate metabolism in the freshwater crab Barytelphusa guerini and in the freshwater clam Anodonta cygnea (Reddy et al, 1989;Hemelraad et al, 1990).…”
Section: Energy Reservesmentioning
confidence: 97%
“…Such energetic expenses may reduce the energy left to invest in reproduction and growth. Several adverse effects of heavy metals on energy expenditure in invertebrates have been reported (Abdullah and Ireland, 1986;Papathanassiou and King, 1986;van Capelleveen, 1987;Naylor et al, 1989;Reddy et al, 1989;Hemelraad et al, 1990) which can likely form traits upon selection which may act. Metal-adapted populations of soil animals have been found at sites known to have been polluted in the recent past, and in mines abandoned for decades (reviewed in Posthuma and van Straalen, 1993).…”
mentioning
confidence: 97%
“…Structural changes in the midgut gland of crustaceans represent a highly sensitive overall response of these organisms to the impact of a contaminant and other exogenous and endogenous factors, such as nutritional and physiological condition (Vogt, 1987). Some studies have demonstrated alterations in this organ due to heavy metal (Papathanassiou & King, 1986;Nicola et al, 1993;Blockwell et al, 1996) and organic contamination (Vogt, 1987;Blockwell et al, 1996). In this context, the use of the midgut gland has been suggested as a`monitoring organ' in toxicological studies (Icely & Nott, 1980;Weeks, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the internal part of marine crustaceans was conducted much earlier, for example, by Couch (1977), who investigated the effect of TBTCl on the gills of the marine shrimp, Penaeus duorarum, and later Griffiths (1980) reported the effects of TBTCl on the gut diverticula of Daphnia magna. Besides that Papathanassiou and King (1986) investigated the effects of TBTCl on the gills and hepatopancreas of the prawn Palaemon serratus, while Papathanassiou and King (1986) reported the effects of TBTCl on the gill cells of the brown shrimp, Crangon crangon. Later, Soegianto et al (1999) investigated the effect of TBTCl on the epithelial cells of gills, hepatopancreas, and epipodites of the late juveniles of Penaeus japonicas, while Wu et al (2009) reported the effects of TBTCl on the gills of a white shrimp, Litopenaeus vannamei.…”
Section: Introductionmentioning
confidence: 99%